A study on factors that influence the performance of TNB Kota Bharu Sdn.Bhd / Sharipah Azlena Syed Hassan - Syed Hassan, Sharipah Azlena (2011)
The study is concentrates on studying the factors that influence performance of the branch. The study is referring to the TNB KOTA BHARU. The purpose of this study is to examine the performance of the company and the most significant factors that influence the performance of the branch. There are 100 respondents selected as the respondents. The respondents selected by using random sampling technique. The data collected by distributing questionnaire, interview and the observation. The data were analyzes by using SPSS Version 14.0 for Windows software programmes, the central of tendency and the dispersion of the data are checked, the reliability and validity of the measures are tested, and the hypotheses developed for this study are also tested. Four techniques are used in analyzing the data for this study, such as frequency analysis, reliability analysis, hypothesis analysis and regression analysis. From the study, the researcher analysis four factors that influence performance TNB Kota Bharu that is staff motivation, working environment, training and skill, and management. From the finding and analysis, only two factors or variables that significant and give relationship to performance of TNB Kota Bharu. Training and skill, and management show significant positive relationship and influence the performance of TNB Kota Bharu